(untitled) (Portuguese Journal of Family Medicine and General Practice, 2020)
Introduction: Chronic obstructive pulmonary disease (COPD) is a preventable respiratory disease, with repercussion in quality of life. Worldwide COPD is a leading cause of mortality. Cigarette smoking is the most debated risk factor, but it’s important to identify other determinants at stake. Family context and behaviors have an impact in the individual’s health. Objective: This systematic review aims to characterize family determinants as possible risk factors for the development of COPD. Methods: A systematic search was conducted in PubMed, followed by a three-step selection process. Data was processed by two independent reviewers and studies were gathered based in pre-defined variables. English written, articles about risk factors for COPD related to the familiar context, meta-analysis, case control, cohort and cross-sectional studies were included. The family determinants considered were childhood maltreatment, education level of the patient, socioeconomic status and family history of tobacco. Results: From 196 references retrieved, inclusion and exclusion criteria were applied, and 8 studies were included. This review found six articles about education, one about socioeconomic status, one about family history of tobacco and one about childhood maltreatment as possible risk factors. One of the studies was a meta-analysis that did not contain any of the other studies included. Conclusions: Little evidence is available on the effect of family determinants in the development of COPD. The studies reported an association between COPD and low socioeconomic status and low education and an interaction with childhood maltreatment. Keywords: chronic obstructive pulmonary disease, family, risk factors